Can Functionally Mature Islet β-Cells be Derived from Pluripotent Stem Cells? A Step Towards Ready-To-Use β-Cells in Type 1 Diabetes - Khand, Bishnu K.; Bhonde, Ramesh R. (Current Stem Cell Research & Therapy, 2021)
Pluripotent Stem Cells [PSCs] are emerging as an excellent cellular source for the treatment of many degenerative diseases such as diabetes, ischemic heart failure, Alzheimer’s disease, etc. PSCderived pancreatic islet β-cells appear to be a promising therapy for type 1 diabetic patients with impaired β-cell function. Several protocols have been developed to derive β-cells from PSCs. However, these protocols produce β-like cells that show low glucose stimulated insulin secretion (GSIS) function and mirror GSIS profile of functionally immature neonatal β-cells. Several studies have documented a positive correlation between the sirtuins (a family of ageing-related proteins) and the GSIS function of adult β-cells. We are of the view that the GSIS function of PSC-derived β-like cells could be enhanced by improving the function of sirtuins in them. Studying the sirtuin expression and activation pattern during the β-cell development and inclusion of the sirtuin activators and inhibitor cocktail (specific to a developmental stage) in the present protocols may help us derive functionally mature, ready-to-use β- cells in-vitro making them suitable for transplantation in type 1 diabetes.
Keywords: Pluripotent Stem Cells (PSCs)